Binary Ce(III) and Li(I) triflate salt composition for solid polymer electrolytes - Alves, Raquel Diana Carneiro (2018)
This study describes the results of the characterization of solid polymer electrolytes using chitosan matrix plasticized with glycerol and doped with cerium and lithium triflates binary salt composition. The electrolytes were prepared by solvent casting method and characterized by thermal analysis (thermogravimetric analysis - TGA and differential scanning calorimetry - DSC), impedance measurements, X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), and electron paramagnetic resonance (EPR). Samples are thermally stable up to 128-153ºC and most of them are amorphous. In some cases, the appearance of crystalline peaks is due to the diffraction of salt domains, which makes the samples less conductive. The room temperature conductivity maximum of 10-6 S cm-1 at 30ºC was obtained for the samples with the same total salts mass of 0.15 g (ChitCeTrif0.05LiTrif0.10 and ChitCeTrif0.10LiTrif0.05). Finally, the EPR analysis suggests that the local coordination environment of the paramagnetic Ce3+ is not the same in different samples. In summary, beside the modest conductivity values of these samples, they are still adequate for some electrochemical applications.